The missense variation Q705K in CIAS1/NALP3/NLRP3 gene and an NLRP1 haplotype are associated with celiac disease. - Pontillo, Alessandra; Vendramin, Anna; Catamo, Eulalia; Fabris, Annalisa; Crovella, Sergio (Am J Gastroenterol, 2011)
OBJECTIVES: Celiac disease (CD) is a multifactorial common disorder with several susceptibility loci. Variations in the NALP1/NLRP1 and NALP3/NLRP3 genes have been reported to confer risk for several autoimmune conditions. We hypothesized that polymorphisms in these genes, due to their role in innate immunity and inflammatory processes, may affect susceptibility to CD. METHODS: Two single-nucleotide polymorphisms (SNPs) in NLRP1 (rs12150220, rs2670660) and two SNPs (rs10754558, rs35829419) in NLRP3 genes were genotyped in 504 CD Italian patients and 256 healthy controls. RESULTS: The minor A allele of NLRP3 rs35829419 (Q705K) polymorphism appeared to exert a protective role against the development of CD (P=0.029; odds ratio (OR)=0.56). Moreover, a particular NLRP1 haplotype was associated with predisposition to CD (P=0.003; OR=1.38), even more when present in combination with the rs35829419 major C allele (P=0.002; OR=1.42). CONCLUSIONS: We hypothesized that the deregulation of CIAS1/NALP3/NLRP3 and NALP1/NLRP1 inflammasomes could have a role in CD pathogenesis.
Keywords: Adaptor Proteins, Signal Transducing; Adolescent; Apoptosis Regulatory Proteins; Carrier Proteins; Celiac Disease; Child; Child, Preschool; Female; Genetic Predisposition to Disease; Genotype; Glutamine; Haplotypes; Humans; Inflammasomes; Italy; Lysine; Male; Mutation, Missense; Polymorphism, Single Nucleotide